Correlation of antioxidant activity and protein alteration of silver BARB protein hydrolysates - Phupaboon, Srisan; Yunchalard, Sirinda; Piyatheerawong, Weera (Asia-Pacific Journal of Science and Technology, 2020)
The antioxidant effects of silver BARB (Barbonymus gonionotus) protein hydrolysates (SBPHs) were investigated under various trypsin and protease treatments. Biochemical characterization and antioxidant activities of 5% (w/v) SBPHs were examined from both fresh fish (FF) and saline-soaked fish (SF) proteins. The highest levels of trichloroacetic acid (TCA)-soluble peptide contents, 57.7 and 58.6 mg/g BARB hydrolysate (BH), were obtained from FF‑trypsin and SF-trypsin, respectively, while the highest levels of free amino nitrogen (FAN) contents, 1.9 and 1.8 µmoL tyrosine/g BH, were respectively found after incubation for 150 min. Additionally, these treatments degraded large proteins into small molecular weights sizes of less than 10.5 kDa after 60 to 150 min of incubation. The highest percentage of 2,2 diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging inhibition of FF-trypsin, 38%, was obtained after 120 min of incubation. Similarly, the highest ferric reducing antioxidant power (FRAP) capacities for both SF-trypsin and FF-trypsin were, respectively, 186.3 and 185.4 µmoL TE/g BH after 120 min of incubation. Furthermore, SF-trypsin exhibited the highest 2,2'‑azino‑bis‑3‑ethylbenzothiazoline-6-sulfonic acid (ABTS) radical-scavenging inhibition, 91.0%, after 90 min of incubation. These results suggest that the by-products of SBPHs obtained from trypsin, especially natural antioxidant compounds, may be useful for consumer health if used in functional foods.